Silicon-carbon negative electrode material with yolk-eggshell structure and preparation method of silicon-carbon negative electrode material
By forming a silicon oxide layer on the surface of photovoltaic silicon waste and covering the amorphous carbon layer, the silicon carbon anode material with an egg yolk-eggshell structure is constructed, the volume expansion problem of the silicon anode material during charging is solved, the circulation performance and safety of lithium batteries are improved, and the production cost is reduced, and the high-value reuse of waste materials is realized.
Patent Information
- Application Number
- CN202411901544.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-21
AI Technical Summary
The volume expansion of traditional silicon negative electrode materials during charging leads to peeling, electrochemical corrosion and short circuit, affecting the safety and service life of lithium batteries.
The silicon carbon negative electrode material with an egg yolk-eggshell structure is used to form a silicon oxide layer on the surface of the photovoltaic silicon waste and coat the amorphous carbon layer to form a core-shell structure, providing a buffer space to overcome the volume effect of silicon.
It improves the cyclic performance and electrochemical performance of silicon-carbon anode materials, reduces production costs, and realizes high-value reuse of waste materials, which has significant economic and social value.
Smart Images

Figure FT_1 
Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new energy materials and energy electrochemistry, and specifically relates to a silicon-carbon negative electrode material with a yolk-eggshell structure and a preparation method thereof. Background Art
[0002] As the world pays more and more attention to environmental protection and sustainable development, the new energy vehicle market has risen rapidly. Consumers have higher requirements for the performance indicators of new energy vehicles such as driving range and charging speed. For example, pure electric vehicles with long driving range are more popular in the market, which requires automotive lithium batteries to have higher energy density.
[0003] Graphite is an ideal negative electrode material. It is widely used in lithium batteries due to its good cycle stability, excellent conductivity and layered structure with good lithium insertion space. However, with the continuous improvement of lithium battery performance requirements, traditional graphite negative electrode materials have been difficult to meet market demand. For example, its gram capacity is low (372mAh / g) and its layered structure is easy to peel off when the number of cycles is large. However, this has also promoted the development of silicon negative electrode materials with higher energy density.
[0004] Silicon has attracted much attention because it can form a binary alloy with lithium and has a high theoretical capacity (4200 mAh / g). Silicon also has a low lithium deintercalation voltage platform and low reactivity with electrolytes, so it is a very promising negative electrode material for lithium batteries. However, silicon has an obvious defect as a negative electrode for lithium batteries. When charging, lithium ions are removed from the positive electrode material and embedded in the lattice inside the silicon crystal, causing a large expansion (about 300%) to form a silicon-lithium alloy. Such a volume effect can easily cause the silicon negative electrode material to peel off from the current collector, resulting in the exposure of the pole foil, causing electrochemical corrosion and short circuit, etc., affecting the safety and service life of the battery. When discharging, lithium ions are removed from the lattice, forming a large gap. And because silicon and carbon are elements of the same main group, a solid electrolyte protective film (SEI film) will also be formed on the silicon surface during the first charge and discharge. However, the peeling caused by the silicon volume effect will cause repeated destruction and reconstruction of the SEI, thereby increasing the consumption of lithium ions and ultimately affecting the capacity of the battery.
[0005] In order to solve the drastic volume effect of silicon, the widely used methods mainly include nano-sizing silicon, designing pore structure materials and silicon-carbon composite materials. Among them, silicon-carbon composite materials combine the advantages of silicon materials and carbon materials, which can maximize their practicality, and the core-shell structure is a common composite type, specifically, carbon materials are wrapped in the outer layer of silicon particles to form a composite material. After the surface of the silicon material is coated with carbon, the conductivity of the material can be enhanced. The carbon material has a certain toughness to avoid the agglomeration between silicon particles and the volume expansion of the material during the lithium insertion and extraction process. At the same time, a SEI film is formed on the surface of the carbon material, which inhibits the corrosion and damage of the electrolyte to the negative electrode material, thereby increasing the cycle life and improving the rate performance. By carbon coating the silicon material and constructing a core-shell structure, it helps to improve the cycle stability of the material.
[0006] Yi Cui et al. reported a yolk-shell structured silicon-carbon anode (A Yolk-Shell Design for Stabilized and Scalable Li-Ion Battery Alloy Anodes, Nano Lett, 2012, 12, 3315-3321.), the core is made of 50-100 nanometer silicon particles, and the shell is amorphous carbon. The outer carbon shell can ensure that electrons are quickly transmitted between particles, and the gap between the core and the shell can provide a buffer space for the expansion of silicon particles, and the structure of the electrode material will not be destroyed during the lithium insertion and extraction process. This design greatly improves the electrochemical performance of silicon. However, since it uses nano-scale silicon powder, the surface defect density of silicon nano-scale is high, and the thermodynamic stability is poor. During the electrochemical cycle, it is easy to agglomerate and cause electrochemical sintering. In addition, nano-silicon has a large contact with the electrolyte, which will lead to more interface side reactions and irreversible capacity loss. In addition, from a purely technological point of view, it needs to be prepared by chemical vapor deposition and magnetron sputtering, which is complex and costly, and difficult to mass produce.
[0007] Compared with nano-scale silicon materials, micron or submicron silicon materials have a smaller specific surface area, will not agglomerate during the electrochemical cycle, have small interfacial side reactions, and have a wide range of sources. They can be directly recycled from the silicon waste generated by silicon wafer cutting in the photovoltaic industry. The photovoltaic industry generates a huge amount of silicon waste each year. If these wastes can be successfully used in lithium-ion batteries, the cost of lithium battery negative electrode materials will be greatly reduced.
[0008] There is no precedent in the existing technology for using photovoltaic silicon waste to produce yolk-eggshell structure silicon-carbon negative electrode materials and successfully applying them to lithium-ion batteries. If successfully developed, it will not only greatly reduce the production cost of silicon-carbon negative electrode materials and realize high-value recycling of waste materials, but will also promote the rapid development of the lithium battery industry and realize important economic and social value. Summary of the invention
[0009] In view of the above-mentioned problems, the present invention aims to provide a silicon-carbon negative electrode material with a yolk-eggshell structure and a preparation method thereof, wherein photovoltaic silicon waste is used as a silicon source, the silicon source is heated in an air atmosphere to form a silicon oxide layer on its surface and then a carbon layer is coated on the outside, and finally the silicon oxide layer is removed to achieve the preparation of the target material. The gap between the core and the shell provides a buffer space for the expansion of silicon particles, which can improve the cycle performance of the silicon-carbon negative electrode material. The preparation process is simple, the cost is low, and it is convenient for large-scale production.
[0010] In order to achieve the above object, the technical solution adopted by the present invention is as follows: a method for preparing a silicon-carbon negative electrode material with a yolk-eggshell structure, comprising the following steps: Photovoltaic silicon waste is used as a silicon source and heated in an air atmosphere to produce a silicon oxide layer on the surface of silicon particles. The resulting material is denoted as Si@SiOx; A carbon shell is coated on the surface of Si@SiOx, which is denoted as Si@SiOx@C; The Si@SiOx@C material is immersed in a hydrofluoric acid solution to remove the silicon oxide intermediate layer, centrifuged and washed to remove the hydrofluoric acid, and dried to obtain a silicon-carbon negative electrode material with a yolk-eggshell structure, which is recorded as Si@Void@C.
[0011] Furthermore, in step 1), the median particle size of the photovoltaic silicon waste is 0.1-5 μm.
[0012] Furthermore, in step 1), the heating temperature is 400-1000° C., the heating reaction time is 1-180 min, and the thickness of the formed silicon oxide layer is 0.1-3 μm.
[0013] Furthermore, in step 2), the carbon shell is formed by mixing the Si@SiOx material with an organic carbon source and then carbonizing the mixture through high temperature sintering.
[0014] Furthermore, the mass ratio of Si@SiOx material to organic carbon source is 30~80:1.
[0015] Furthermore, the organic carbon source is one or a combination of at least two of coal tar, coal pitch, petroleum pitch, epoxy resin, phenolic resin, acrylic resin, furfural resin, polyvinyl chloride, polyacrylonitrile and polyvinylidene fluoride.
[0016] Furthermore, the carbonization process is carried out under a protective gas atmosphere, with a heating rate of 1-20°C / min, a carbonization temperature of 500-1250°C, and a carbonization time of 1-20 h.
[0017] Furthermore, in step 3), the mass fraction of the hydrofluoric acid solution is 1-40%, the immersion time is 10-180 min, the drying temperature is 50-100° C., and the drying time is 1-20 h.
[0018] The silicon-carbon negative electrode material prepared according to the above method is a silicon-carbon composite material with a yolk-eggshell structure, wherein the core is made of micron-sized silicon particles, the shell is amorphous carbon, and there is a void space between the silicon particles and the carbon shell. The prepared silicon-carbon negative electrode material is coated on the surface of the current collector to form a negative electrode, and assembled with the positive electrode to prepare a high-performance lithium-ion battery.
[0019] The beneficial effects of the present invention are: 1. The silicon-carbon negative electrode material prepared in the present application is a silicon-carbon composite material with a yolk-eggshell structure. The core is made of micron-sized silicon particles, the shell is amorphous carbon, and there is a reasonably designed void space between the particles and the shell. The clearly defined void space can overcome the drastic volume effect of the silicon material as a lithium ion negative electrode during the charge / discharge process, and will not destroy the carbon shell during the lithium insertion and extraction process, thereby stabilizing the solid electrolyte intermediate phase on the shell surface, so that the electrochemical performance of the lithium battery prepared based on it is greatly improved; 2. This application adopts a simple high-temperature oxidation method to controllably form a silicon oxide layer of a certain thickness on the surface of photovoltaic silicon waste, which not only provides a basis for the subsequent generation of void space between silicon particles and carbon layers, but also removes a layer of organic matter adhering to the surface of silicon waste by means of high temperature, thereby purifying photovoltaic silicon waste, making the performance of the negative electrode material obtained subsequently more perfect. This processing method is simple and easy to operate, which is conducive to the large-scale production of this silicon-carbon negative electrode material; 3. This application uses photovoltaic silicon waste as the silicon source, which not only has extremely high-purity silicon, but also has a wide source and low price. It can significantly reduce the production cost of silicon-carbon negative electrode materials, and can also simultaneously achieve high-value transformation and utilization of waste resources, and has obvious economic and social value. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a charge and discharge cycle curve diagram of the negative electrode material obtained in the embodiment and the comparative example. DETAILED DESCRIPTION
[0021] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0022] The median particle size (D50) of the photovoltaic silicon waste used in the examples and comparative examples is 0.1-5 μm. Example 1
[0023] This embodiment discloses a method for preparing a silicon-carbon negative electrode material with a yolk-eggshell structure, and the specific preparation process is as follows: S1. Put the sagger containing 1 kg of photovoltaic silicon waste into a push plate furnace, let in air, and react at 700°C for 30 min to form a silicon oxide layer with a thickness of about 0.1-3 μm on the surface of the silicon particles. Then remove the sagger and the obtained material is recorded as Si@SiOx. S2, weighing 1 kg of the Si@SiOx material prepared in step S1, and mixing it with 0.2 kg of coal tar pitch through a VC mixer, the speed during the mixing process is 800 rpm, and the mixing time is 60 min, and the mixture is moved to a push plate furnace for carbonization treatment to coat a layer of carbon material on the surface of the Si@SiOx material, the carbonization process is carried out under a protective atmosphere, the heating rate is 10°C / min, the carbonization temperature is 1000°C, and the carbonization time is 6 h. The obtained material is recorded as Si@SiOx@C; S3. Prepare a hydrofluoric acid solution with a mass fraction of 5%, soak the Si@SiOx@C material prepared in step S2 in the hydrofluoric acid solution for 2 h to remove the silicon oxide layer, centrifuge, wash with anhydrous ethanol 3-5 times to remove the hydrofluoric acid, and dry in a vacuum drying oven at 80°C for 8 h to obtain a silicon-carbon negative electrode material with a yolk-eggshell structure, recorded as Si@Void@C.
[0024] Comparative Example 1 The difference between this comparative example and Example 1 is that the photovoltaic silicon waste is not subjected to heat treatment to form a silicon oxide layer thereon, but a silicon-carbon composite material Si@C is prepared by directly forming a carbon coating layer on the surface of the silicon material. The specific preparation process is as follows: 1 kg of photovoltaic silicon waste and 0.2 kg of coal tar were mixed in a VC mixer at a speed of 800 rpm and a mixing time of 60 min. The mixture was moved to a push plate furnace for carbonization treatment to coat a layer of carbon material on the surface of the Si material. The carbonization process was carried out under a protective atmosphere at a carbonization temperature of 1000 °C and a carbonization time of 6 h. The obtained material was recorded as Si@C.
[0025] Comparative Example 2 The difference between this comparative example and Example 1 is that hydrofluoric acid is not used to remove the silicon oxide layer on the silicon surface, that is, a composite material with no gaps between silicon and carbon is obtained. The specific preparation scheme is as follows: S1. Put the sagger containing 1 kg of photovoltaic silicon waste into a push plate furnace, let in air, and react at 700°C for 30 min to form a silicon oxide layer of a certain thickness on the surface of the silicon particles. Then remove the sagger and the obtained material is recorded as Si@SiOx. S2. Weigh 1 kg of the Si@SiOx material prepared in step S1 and mix it with 0.2 kg of coal tar pitch through a VC mixer. The speed during the mixing process is 800 rpm and the mixing time is 60 min. Move the mixture to a push plate furnace for carbonization treatment to coat a layer of carbon material on the surface of the Si@SiOx material. The carbonization process is carried out under a protective atmosphere. The heating rate is 10°C / min, the carbonization temperature is 1000°C, and the carbonization time is 6 h. The obtained material is recorded as Si@SiOx@C.
[0026] The materials prepared in Example 1 and Comparative Examples 1-2 were used as battery negative electrodes, respectively. After batteries were assembled into batteries according to the same assembly process, the electrochemical properties of the batteries were tested. The test results are shown in Table 1.
[0027] Table 1. Electrochemical performance of lithium batteries based on negative electrode materials prepared in Example 1 and Comparative Examples 1-2
[0028] As can be seen from Table 1, the yolk-eggshell structured silicon-carbon material prepared in Example 1 has excellent cycle performance, with a retention rate of 94.11% after 100 cycles, indicating that the gap between the yolk and the eggshell provides a buffer space for the expansion of silicon particles, and does not cause the silicon particles to break and pulverize during the lithium insertion and extraction process, and can maintain a complete conductive environment, and the outer carbon shell can ensure that electrons are quickly transmitted between particles. The materials prepared in Comparative Examples 1 and 2 are prone to silicon particle pulverization during the cycle, which leads to rapid attenuation of electrochemical performance.
[0029] The above shows and describes the basic principles, main features and advantages of the present invention. However, the above is only a specific embodiment of the present invention, and the technical features of the present invention are not limited thereto. Any other implementation methods derived by any technician in the field without departing from the technical solution of the present invention should be included in the scope of the present invention.
Claims
1. A method for preparing a silicon-carbon negative electrode material with a yolk-eggshell structure, characterized in that: The steps include: Photovoltaic silicon waste is used as a silicon source and heated in an air atmosphere to produce a silicon oxide layer on the surface of silicon particles. The resulting material is denoted as Si@SiOx; A carbon shell is coated on the surface of Si@SiOx, which is denoted as Si@SiOx@C; The Si@SiOx@C material is immersed in a hydrofluoric acid solution to remove the silicon oxide intermediate layer, centrifuged and washed to remove the hydrofluoric acid, and dried to obtain a silicon-carbon negative electrode material with a yolk-eggshell structure, which is recorded as Si@Void@C.
2. The method for preparing a silicon-carbon negative electrode material with a yolk-eggshell structure as claimed in claim 1, characterized in that: In step 1), the median particle size of the photovoltaic silicon waste is 0.1-5 μm.
3. The method for preparing a silicon-carbon negative electrode material with a yolk-eggshell structure according to claim 1, characterized in that: In step 1), the heating temperature is 400-1000° C., the heating reaction time is 1-180 min, and the thickness of the formed silicon oxide layer is 0.1-3 μm.
4. The method for preparing a silicon-carbon negative electrode material with a yolk-eggshell structure according to claim 1, characterized in that: In step 2), the carbon shell is formed by mixing the Si@SiOx material with an organic carbon source and then carbonizing it by high temperature sintering.
5. The method for preparing a silicon-carbon negative electrode material with a yolk-eggshell structure as claimed in claim 4, characterized in that: The mass ratio of Si@SiOx material to organic carbon source is 30~80:
1.
6. The method for preparing a silicon-carbon negative electrode material with a yolk-eggshell structure as claimed in claim 4, characterized in that: The organic carbon source is one or a combination of at least two of coal tar, coal pitch, petroleum pitch, epoxy resin, phenolic resin, acrylic resin, furfural resin, polyvinyl chloride, polyacrylonitrile and polyvinylidene fluoride.
7. The method for preparing a silicon-carbon negative electrode material with a yolk-eggshell structure as claimed in claim 4, characterized in that: The carbonization process is carried out under a protective gas atmosphere, with a heating rate of 1-20°C / min, a carbonization temperature of 500-1250°C, and a carbonization time of 1-20 h.
8. The method for preparing a silicon-carbon negative electrode material with a yolk-eggshell structure as claimed in claim 1, characterized in that: In step 3), the mass fraction of the hydrofluoric acid solution is 1-40%, the immersion time is 10-180 min, the drying temperature is 50-100° C., and the drying time is 1-20 h.
9. A silicon-carbon negative electrode material with a yolk-eggshell structure, characterized in that: It is prepared based on the preparation method described in any one of claims 1 to 8. The core of the silicon-carbon negative electrode material is made of micron-sized silicon particles, the shell is amorphous carbon, and there is a void space between the silicon particles and the shell.
10. A lithium ion battery, characterized in that: It comprises a positive electrode and a negative electrode, wherein the negative electrode comprises a current collector and the silicon-carbon negative electrode material as claimed in claim 9 coated on the surface of the current collector.
Citation Information
Cited By
Egg yolk-eggshell structure silicon carbon negative electrode material and preparation and application thereof
CN121076086A